Employing Graphic Organizers through Team-Pair-Solo Strategy to Improve Reading Comprehension of Eighth Graders at SMPN 9 Kubung - Satriyani, Lina; Moerdibjon, Arwijati Wahjudi; Prayogo, Johannes Ananto (AT-TA'LIM, 2016)
This research was conducted to improve the students’ reading comprehension by employing graphic organizers through Team-Pair-Solo strategy. Classroom Action Research which involved 32 eighth graders was employed in this study. The instruments were reading comprehension test, observation checklists, field notes and questionnaire. The steps done in employing the strategy were: (1) working in group in comprehending the text, (2) discussing the answer, (3) working in pairs,(4) creating their own graphic organizers, (5) swapping their work (6) giving feedback, (7) discussing the feedback (8) revising individually, (9) retelling the text by using their graphic organizers. The findings of this study showed that the strategy improved students’ ability; most of the students (87.5%) were actively involved and enthusiastic in teaching-learning process; and most of them (90%) gave positive perceptions toward the implementation of the strategy. These results indicated that the strategy was effective in improving students’ reading comprehension ability.